Split Products of Fibrinogen after Prolonged Interaction with Plasmin - Niléhn, J.-E (Thrombosis and Haemostasis, 1967)
End split products of fibrinogen after prolonged interaction with plasmin were separated on DEAE-cellulose. The D and E compounds measured with light ab- sorbancy constituted about 75% respectively 10% of the end split products.The D product was separated by electrophoresis into 8 components with slight difference in charge and all of them carried the same antigenic determinants. All components were found in plasmin digested fibrinogen prepared from a pool and from single donors. Four of the ∼D components were predominant. The sedimentation coefficient of the D preparation with these 4 components was 5.3 and the fraction sedimented as an homogenous peak. Slight heterogeneity of the preparation was, however, found on determination of the diffusion coefficient. The molecular weight was calculated as 80,000. On gel filtration of the D fraction on Sephadex G 200, the D products were eluted in the beginning of the albumin peak. It is suggested that the D product which is practically homogenous on ultracentrifugation dissociates on electrophoresis. The combination of the electrophoretic, immunologic and ultracentrifugal data suggests that the fibrinogen molecule consists of a series of similar repetitive units.The E product was homogenous in the ultracentrifuge and on electrophoresis. The sedimentation coefficient was 3.3 and the molecular weight was estimated to 40,800.On filtration through Sephadex G 200 the E product was hardly distinguishable from the D product and was eluted together with the ablumin.